2022
DOI: 10.1159/000522584
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Extracellular Vesicles Derived from HIF Prolyl Hydroxylase Domain Enzyme Inhibitor-Treated Cells on Renal Ischemia/Reperfusion Injury

Abstract: <b><i>Introduction:</i></b> Acute kidney injury (AKI) is a major public health problem worldwide. However, there is no definitive therapies to treat established AKI. In this study, we used FG-4592 to induce hypoxia inducible factor (HIF) expression in cells and then explored whether the extracellular vesicles (EVs) secreted by HIF-upregulated cells could alleviate ischemia/reperfusion injury (IRI)-induced AKI. <b><i>Methods:</i></b> FG-4592/HK2-EVs and FG-4592/HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…He mainly focused on the association of EVs with kidney-related diseases (AKI, CKD, renal inflammation and fibrosis, diabetic nephropathy, etc.). Moreover, he and his colleagues (Lv Lin-li, top 2; Wang Bin, top 3; Tang Tao-tao, top 10; Li Zuo-lin, top 9) also contributed to the correlation between EV and kidney-related disease research ( Lv et al, 2018a ; Tang et al, 2019a ; Wang et al, 2019a ; Tang et al, 2019b ; Lv et al, 2019 ; Tang and Liu, 2019 ; Tang et al, 2020a ; Tang et al, 2020c ; Wang et al, 2020 ; Cao et al, 2021a ; Feng et al, 2021a ; Feng et al, 2021b ; Tang et al, 2021 ; Ding et al, 2022 ; Tang et al, 2022 ). Interestingly, these researchers not only had the biggest collaboration network and active teamwork in this field but also the longest period in publication and the highest number of impact measures.…”
Section: Discussionmentioning
confidence: 99%
“…He mainly focused on the association of EVs with kidney-related diseases (AKI, CKD, renal inflammation and fibrosis, diabetic nephropathy, etc.). Moreover, he and his colleagues (Lv Lin-li, top 2; Wang Bin, top 3; Tang Tao-tao, top 10; Li Zuo-lin, top 9) also contributed to the correlation between EV and kidney-related disease research ( Lv et al, 2018a ; Tang et al, 2019a ; Wang et al, 2019a ; Tang et al, 2019b ; Lv et al, 2019 ; Tang and Liu, 2019 ; Tang et al, 2020a ; Tang et al, 2020c ; Wang et al, 2020 ; Cao et al, 2021a ; Feng et al, 2021a ; Feng et al, 2021b ; Tang et al, 2021 ; Ding et al, 2022 ; Tang et al, 2022 ). Interestingly, these researchers not only had the biggest collaboration network and active teamwork in this field but also the longest period in publication and the highest number of impact measures.…”
Section: Discussionmentioning
confidence: 99%
“…Roxadustat protects against renal ischemia/reperfusion injury by inhibiting inflammation (Miao et al, 2021). And it also reported that extracellular vesicles (EVs) derived from HK2 or HEK293 cells after roxadustat treatment could alleviate renal tubular injury and inflammation, suggesting a novel therapeutic role of roxadustat/EVs in the treatment of AKI (Ding et al, 2022). The pretreatment of roxadustat improved the creatinine elevation and renal tubular injuries induced by ischemia.…”
Section: Roxadustat and Diabetic Nephropathymentioning
confidence: 96%
“…Supramolecular nanofibers containing arginine-glycine-aspartate (RGD) peptides improved the therapeutic effects of EVs in kidney repair [132], and platelet-rich plasma induced YAP nuclear expression to promote BMMSC proliferation, activating the AKT/Rab27 pathways to facilitate the paracrine secretion of MSC-derived exosomes for glycerol-induced AKI repair [133]. Additionally, hypoxia-induced activation of HIF-1α was also found to increase the loading of miR-21 in exosomes, thereby providing a therapeutic effect against septic/IRI-induced AKI [134].…”
Section: Exosome Modificationsmentioning
confidence: 99%